Integrated Ray Tracing Model for End-to-end Performance Verification of Amon-Ra Instrument - Jae-Min Lee; Won Hyun Park; Sun-Jeong Ham; Hyun-Su Yi; Jee Yeon Yoon; Sug-Whan Kim; Ki-Hyuk Choi; Zeen Chul Kim; Mike Lockwood (Journal of Astronomy and Space Sciences, 2007)
The international EARTHSHINE mission is to measure 1% anomaly of the Earth global albedo and total solar irradiance using Amon-Ra instrument around Lagrange point 1. We developed a new ray tracing based integrated end-to-end simulation tool that overcomes the shortcomings of the existing end-to-end performance simulation techniques. We then studied the in-orbit radiometric performance of the breadboard Amon-Ra visible channel optical system. The TSI variation and the Earth albedo anomaly, reported elsewhere, were used as the key input variables in the simulation. The output flux at the instrument focal plane confirms that the integrated ray tracing based end-to-end science simulation delivers the correct level of incident power to the Amon-Ra instrument well within the required measurement error budget of better than ±0.28%. Using the global angular distribution model (ADM), the incident flux is then used to estimate the Earth global albedo and the TSI variation, confirming the validity of the primary science cases at the L1 halo orbit. These results imply that the integrated end-to-end ray tracing technique, reported here, can serve as an effective and powerful building block of the on-line science analysis tool in support of the international EARTHSHINE mission currently being developed.